Spatial-Link: Bridging Understanding of Bilateral Cooperation Through Virtual Space Technology - Rangga Widiyono Yanuarta; Bunda Harini; Siti Dewi Maharani; Budiansyah; Mazda Leva Okta Safitri; Muhammad Ittihadul Umam; Ilham Arya Susanto (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2026)
This study aims to produce a metaverse-based learning media product assisted by the Spatial application on bilateral cooperation material in grade VI of SD Negeri 11 Indralaya. This learning media was developed using the ADDIE development model consisting of five stages, namely analyze, design, develop, implement, and evaluate. The validation results carried out by three validators showed that the developed learning media obtained an average score of 94.82% which is categorized as very feasible and valid for use in the implementation stage. Then, a practicality test was conducted by giving a questionnaire to 25 grade VI students. The results of the practicality test showed that the total score obtained was 248 out of a maximum score of 250 with a percentage of 99.2%, which is included in the very practical category. Based on these results, it can be concluded that the metaverse-based learning media assisted by the Spatial application is feasible to be used in the learning process on bilateral cooperation material in grade VI of SD Negeri 11 Indralaya.